2004
DOI: 10.3168/jds.s0022-0302(04)73233-6
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Inflammatory Reaction During Experimental Escherichia coli Mastitis in Primiparous Cows

Abstract: Nineteen primiparous cows were experimentally infected in 2 quarters with 1 × 10 4 (group A) or 1 × 10 6 (group B) cfu of Escherichia coli P4:O32 per quarter within 2 to 4 wk after parturition. Blood and milk samples were collected from all primiparous cows at regular time intervals from d −4 to d +3 relative to inoculation. Milk production rapidly decreased in both groups during E. coli mastitis, but recovery appeared to be faster in group B at d + 1 postinfusion (p.i.). The milk production losses in the noni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
45
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 32 publications
9
45
1
Order By: Relevance
“…Possibly, in these sows there may be abundant and regulated release of anti-inflammatory mediators [40,53], limiting the production of the inflammatory cytokines. However, in accordance with our results, previous studies in cows have shown a significant increase in the proinflammatory cytokines at the level of both mRNA [33,37] and protein [6,11,26,32,45,48,54] in either mammary tissues or milk collected from the infected glands following intramammary inoculation with E. coli. The results here indicate that the development of clinical symptoms of coliform mastitis in the sow is associated with a locally increased proinflammatory cytokine production in response to intramammary E. coli infection.…”
Section: Discussionsupporting
confidence: 93%
“…Possibly, in these sows there may be abundant and regulated release of anti-inflammatory mediators [40,53], limiting the production of the inflammatory cytokines. However, in accordance with our results, previous studies in cows have shown a significant increase in the proinflammatory cytokines at the level of both mRNA [33,37] and protein [6,11,26,32,45,48,54] in either mammary tissues or milk collected from the infected glands following intramammary inoculation with E. coli. The results here indicate that the development of clinical symptoms of coliform mastitis in the sow is associated with a locally increased proinflammatory cytokine production in response to intramammary E. coli infection.…”
Section: Discussionsupporting
confidence: 93%
“…Clinical scores, combining several clinical parameters, have been described (Wenz et al, 2001;Friton et al, 2002;Vangroenweghe et al, 2004a). Using the clinical severity score described by Vangroenweghe et al (2004a), carprofen-treated animals had a significantly lower clinical score at PIH 12 and 15 compared with the saline-treated group (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Using the clinical severity score described by Vangroenweghe et al (2004a), carprofen-treated animals had a significantly lower clinical score at PIH 12 and 15 compared with the saline-treated group (Table 3). Although, as expected from previous trials, all animals in both groups responded mildly to moderately following E. coli challenge, the carprofen-treated animals generally showed a lower clinical severity score within 3 h of NSAID administration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations